A proposed pediatric oncology center : specialized hospital for children with cancer: an integration of therapeutic environment and positive distraction - Belmonte, Jeanne L. (Manila : National University, 2018)
This study delves in understanding different factors that relates to pediatric cancer; the different types of pediatric cancer, the treatment process, state-of-the-art equipment's or facilities and different planning and design approach to create a therapeutic environment for the patients.
Chapter 1. The problem and its setting -- Chapter 2. Review of Related literature -- Chapter 3. Research methodology -- Chapter 4. Data gathering, collation and analysis data -- Chapter 5. Design development -- Chapter 6. Translation -- Bibliography -- Annexes.
Includes bibliographical references.
Keywords: PEDRIATIC ONCOLOGY CENTER -- PLANNING